2019
DOI: 10.18203/2394-6040.ijcmph20194524
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito density in rural Kerala: a study on the trend of Aedes larval indices over monsoon in a rural area of Thrissur district, India

Abstract: Background: Dengue is one of the most rapidly spreading mosquito-borne viral diseases in the world. Aedes aegypti mosquito is the main vector of dengue and Chikungunya. Entomological surveillance on Aedes mosquito has been standardized on different indices like House index, Container index, Breteau index. Larval indices are important predictors of outbreaks and are valuable in taking preventive measures. The objectives of the present study was to study the trend of larval indices over four months in selected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…(10) Another study done in Thrissur district also showed a peak in larval indices during the month of June. (11) In present study, after intervention in Feb 2020 BI came to 2.5%. Similar finding were noted in a study conducted in Karnataka.…”
Section: Discussionsupporting
confidence: 44%
“…(10) Another study done in Thrissur district also showed a peak in larval indices during the month of June. (11) In present study, after intervention in Feb 2020 BI came to 2.5%. Similar finding were noted in a study conducted in Karnataka.…”
Section: Discussionsupporting
confidence: 44%